2010
DOI: 10.1039/b913859e
|View full text |Cite
|
Sign up to set email alerts
|

Acetylenedithiolate as directional bridging ligand in cobalt(i) alkyne platinumdithiolato bimetallic complexes

Abstract: The eta(2)-C,C-acetylenedithiolate (acdt2-) complex K[(triphos)Co(acdt)], K-5, {triphos = 1,1,1-tris(diphenylphosphinomethyl)ethane} was obtained by consecutive removal of S-protection groups in [(triphos)Co(1)]PF6, 3-PF6 (1 = 1-Trimethylsilyl-7-phenyl-3,6-dithiahept-4-ine). Reaction of K-5 with selected Pt(II) salts resulted in the formation of the new heterobimetallic complexes [(phen)Pt(5)]BPh4, 6-BPh4, (phen = 1,10-phenanthroline) and [(dppe)Pt(5)]BPh4, 7-BPh4, {dppe = 1,2-bis(diphenylphosphino)ethane}, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The structure of 2 (Figure ) shows the presence of a dimer in which the C 2 S 2 2− ligand bridges the two Yb III ions in an unprecedented linear μ‐η 2 ‐C,S: η 2 ‐C′,S′ fashion. The observed binding mode is consistent with the formulation of the ligand acetylenedithiolate and differs significantly from the side‐on bridging mode (μ‐η 2 ‐C,C′) found in homo‐ and heterobimetallic complexes of d‐block metals …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The structure of 2 (Figure ) shows the presence of a dimer in which the C 2 S 2 2− ligand bridges the two Yb III ions in an unprecedented linear μ‐η 2 ‐C,S: η 2 ‐C′,S′ fashion. The observed binding mode is consistent with the formulation of the ligand acetylenedithiolate and differs significantly from the side‐on bridging mode (μ‐η 2 ‐C,C′) found in homo‐ and heterobimetallic complexes of d‐block metals …”
Section: Figurementioning
confidence: 99%
“…The value of the C−C bond distance in the C 2 S 2 2− moiety [1.16(2) Å] is characteristic of a triple bond (1.2 Å in acetylene) and is slightly shorter than what found in other Ln III ‐bound acetylides [1.202(4) Å] . The two C−S bonds [1.71(2) and 1.72(2) Å] are longer than the CS double bond in CS 2 (1.55 Å) and in the range of values previously reported for the C−S bond in ethylenedithionate complexes . The mean value of the Yb III −C bond distance at 2.62(2) Å is shorter than the value found in the Yb III η 2 ‐acetylene complex [(Me 5 C 5 ) 2 Yb(η 2 ‐MeC≡CMe) [2.850(1) Å] but consistent with the difference in ionic radii (0.16 Å).…”
Section: Figurementioning
confidence: 99%
“…In the course of our studies with sulfide-substituted alkynes [7] we observed a cyclodimerization reaction of two internal dithioalkynes at the [(C 5 H 5 )ReBr 2 ] fragment leading to a folded ReC3 ring skeleton. This finding is surprising because investigations by Green et al with the identical metal complex system but diphenylacetylene showed the formation of a stable η 4 -cyclobutadiene complex.…”
Section: Introductionmentioning
confidence: 97%